GIS-based Flood Susceptibility Mapping Using Overlay Method in Central Sulawesi - Rheinhart Christian Hutauruk; Solih Alfiandy; Hermanto Asima Nainggolan; Mas Harya Fitra Yudo Raharjo (Forum Geografi, 2020)
Central Sulawesi is the largest province on the Sulawesi island with a dominant sloping topographic condition and has a variety of soil types, flow density, land use and rainfall that makes this region vulnerable to flooding. Flooding is a hydrometeorological disaster that will adversely affect aspects of human life such as social and economic activities in an area because it can cause environmental damage, casualties and disrupt economic activity. Because of its enormous impact, the purpose of this research study is to find out areas in the province of Central Sulawesi that are suscept to flooding. The method used in this research study is scoring the classification of flood hazard parameters such as slope level, elevation, soil type, rainfall, land use and flow density which are then overlay using ArcGis 10.2.2. The results obtained that the province of Central Sulawesi has three categories of areas suscept to flooding with a low category 6630.3 km2, moderate 46081.9 km2 and high category 7104.7 km2. Based on the results and discussion, it can be concluded that Central Sulawesi province has a dominant level of vulnerability which is moderate.